HERMENEUTICAL APPROACH TO THE QUR’AN - Ismail Suardi Wekke; Acep; Firdaus (IAIN Tulungagung, 2018)
This paper discusses the contribution of a prolific author and an Egyptian scholar Nasr Hamid Abu Zayd and his hermeneutical approach to the Qur’an. The article argues that Abu Zayd is a Muslim reformer of the twentieth century through his takwil (hermeneutical concept). His hermeneutical concept is questioning the “an-nash (textual)” tradition of the Qur’an and the transformation of Arab culture from oral to text-oriented culture in the earliest history of the Qur’an. He differentiates between tanzil (message sent to man) to takwil (interpretation of the message). This article further argues that Abu Zayd’s hermeneutical concept should be understood from the history of revelation which speaks to a particular community and respond to a particular situation. Thus, the Qur’an itself is a living phenomenon and open for interpretation, rather than a closed corpus.